Establishing critical limits of sulphur for groundnut (Arachis hypogaea) - KUMAR, RAHUL; HAZRA, G C; DAS, RUMA; MAJUMDER, S P; PADHAN, DHANESHWAR; DAS, A C (The Indian Journal of Agricultural Sciences, 2019)
Sulphur is essential for growth and development of groundnut (Arachis hypogaea L.). Deficiency of S is widespread in soils of India, and is becoming a major concern for the quality and yield of groundnut crop. Therefore, a study was conducted to investigate the response of groundnut to S application in alluvial Inceptisols of West Bengal with four levels of S, i.e. 0, 15, 30 and 45 kg/ha. The critical limits of Sulphur in soil and plant for deï¬ciency, adequacy and toxicity were determined from Bray percent yield (BPY). The amount of CaCl2 extractable S in soils varied from11.90â€“29.17 mg/kg while the critical level for deficiency of S in groundnut was graphically 18.6 mg/kg and statistically 19.58 mg/kg in soils. Application of S increased groundnut yield signiï¬cantly, concentration of S in plant and its uptake by groundnut parts. The critical limit was determined to be 3.0 g/kg for groundnut plants and 4.42 g/ kg for groundnut nuts at harvest.